Design of Decision Support System in the Metastatic Colorectal Cancer Data Set and Its Application - Pala, Tuba; Çamurcu, Ali Yılmaz (Bajece, 2016)
Developing the system which will help doctors with the result to be obtained from the medical data sets by realizing the design of the medical decision support system in which data mining methods are used is the primary objective of this study.
Keywords: Medical Decision Support System; Data Mining; Classification; K-Means Clustering; Metastatic Colorectal Cancer Disease Data Set